Pemilihan Vendor Dalam Proyek Mud Removal Pada Tambang Batu Bara (Studi Kasus PT. Darma Henwa) (Journal of Entrepreneurship, Management and Industry (JEMI), 2023)
This study aims to identify the criteria used in determining vendors for the mud removal project in a coal mine using the Analytical Hierarchy Process (AHP) method. Another objective is to determine the best vendor for the project based on the AHP method. PT. Darma Henwa, Tbk, as one of the leading mining contractor services in Indonesia, needs to improve efficiency and effectiveness in carrying out coal mining operations in order to remain competitive and increase business revenue.The results of the study show that the criteria used for selecting mud removal project service providers in the coal mine are Service/Experience, Contract and Commercial, and Machine/Manufacturing. Based on the overall calculations, Alternative 3 obtained the highest score of 23.273% and ranked first. Alternative 2 obtained a score of 23.089% and ranked second, followed by Alternative 4 with a score of 17.190% and ranked third. Alternative 1 obtained a score of 16.686% and ranked fourth, while Alternatives 5 and 6 scored 11.147% and 8.616% respectively, ranking fifth and sixth. This indicates that PT. Darma Henwa, Tbk prefers Alternative 3 as the best vendor based on all the criteria used.In this study, the Analytical Hierarchy Process (AHP) method was successfully applied to determine the best vendor for the mud removal project in the coal mine. The AHP method was used to calculate the weights of criteria and vendor alternatives based on expert assessments. The criteria used were Service/Experience, Contract and Commercial, and Machine/Manufacturing. The evaluated vendor alternatives were Alternative 1 to Alternative 6. This study used the Analytical Hierarchy Process (AHP) method to determine the best vendor for the mud removal project in the coal mine. The criteria used were Service/Experience, Contract and Commercial, and Machine/Manufacturing. Based on the AHP analysis results, Alternative 3 was selected as the best vendor with an AHP value of 23.273%. Alternative 2 ranked second with a value of 23.089%. The Service/Experience criterion had the highest weight with a value of 0.568, followed by the Contract and Commercial criterion with a weight of 0.334, and the Machine/Manufacturing criterion with a weight of 0.098. The recommendation provided is to choose Alternative 3 as the best vendor while considering other relevant aspects for the company.Keywords: Vendor Selection; Mud Removal Projects; Analytical Hierarchy Process (AHP)